Transcendence and Immanence: Deciphering Their Relation through the Transcendentals in Aquinas and Kant - Hampton, Alexander J. B. ca. 20./21. Jh. (Toronto journal of theology, 2018)
This article examines the relationship between the conspicuous and complicated terms of transcendence and immanence, which may equally be defined as essentially connected or diametrically opposed. Recent developments in two largely unrelated sets of scholarship-the re-evaluation of secularization, and the relationship between medieval and modern philosophy-provide a helpful means to arrive at a clearer understanding of this challenging problem. Charles Taylor and Jan Aertesn act as foci for these developments, particularly through their respective concerns with epistemic framing in relation to transcendence and immanence, and the role of transcendentals in medieval philosophy. This examination brings these two concepts together, examining the idea of transcendentals offered by both Aquinas, a thinker of the transcendent frame, and Kant, a thinker of the immanent frame. From this juxtaposition, we can offer two contrasting understandings of the relationship between transcendence and immanence from within both the transcendent and immanent frames. Finally, two brief literary examples demonstrate how these two ways of reading transcendence and immanence may be employed in the contextual understanding of religious writing. To understand the unity and division between transcendence and immanence is to better comprehend two primary terms in the study of religion and to appreciate a fundamental development in the history of religion in the West.